2022
DOI: 10.3389/fphar.2022.1015693
|View full text |Cite
|
Sign up to set email alerts
|

Dehydromiltirone inhibits osteoclast differentiation in RAW264.7 and bone marrow macrophages by modulating MAPK and NF-κB activity

Abstract: Background: Osteoporosis is a type of systematic metabolic bone disease caused by the decrease in osteogenic activity or excessive resorption of bone with the relative enhancement of osteoclast function. As osteoporosis seriously affects the quality of patients’ life, effective drugs are needed to treat this disease. Based on the combination of network pharmacology and cellular studies, this study aimed to investigate the probable mechanism of Dehydromiltirone (DHT) in the treatment of osteoporosis.Method: The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…RANK signaling is activated by RANKL via TRAF6, which, in turn, induces MAPK or NF-κB activation. Hence, the MAPK and NF-κB axes are crucial for modulating osteoclast differentiation in skeletal development and homeostasis (23)(24)(25)(26)(27)(28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…RANK signaling is activated by RANKL via TRAF6, which, in turn, induces MAPK or NF-κB activation. Hence, the MAPK and NF-κB axes are crucial for modulating osteoclast differentiation in skeletal development and homeostasis (23)(24)(25)(26)(27)(28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, FOXP1 facilitates osteogenic differentiation of adipose-derived mesenchymal stem cells and bone regeneration in osteoporosis [ 41 ]. Phosphorylation of MAPK14 benefits the osteogenic differentiation of human mesenchymal stem cells [ 42 ], and inhibits the osteolytic differentiation of bone marrow macrophages [ 43 ]. It is strongly indicated that M0-exo, M1-exo and M2-exo are most likely involved in the OTM process by transporting these DE-miRNAs to achieve regulation of osteogenic differentiation of hPDLSCs.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of two compounds on cell activity was tested by a CCK8 assay according to ref. [40]. Normal cultures of RAW264.7 cells were passaged for more than 3 times, counted, and adjusted to a cell density of 1 × 10 5 cells/mL, seeded in 100 µL cell suspension per well in 96-well plates and incubated for 20 h in a 37 • C incubator.…”
Section: Cell Culture and Viability Assaymentioning
confidence: 99%
“…Inflammatory factors were detected by Griess kit or ELISA kit. RAW 264.7 cells were delivered, counted, adjusted the cell density to 3 × 10 5 cells/mL, 2 mL/well into 6-well culture plate for 20 h, grouped according to Table 1 and cultured for 20 h. After incubation, the supernatant solution was collected, centrifuged at 1200 rpm for 10 min, and the NO, TNF-α, IL-6 and IL-1β concentration in the cell supernatant was detected using the NO kit and ELISA kit according to the specification and the published papers [39,40]. To detect the expression of COX-2, iNOS, and p-p65, normally cultured RAW 264.7 cells were counted, and their cell density adjusted to 5 × 10 5 cells/mL, followed by 20 h of a 2 mL/well inoculation into 6-well culture plates.…”
Section: Assay Of Nitric Oxide Concentration Tnf-α Il-6 and Il-1βmentioning
confidence: 99%
See 1 more Smart Citation